Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Find the slope of the curve at the given point P and an equation of the tangent line at P.?

Find the slope of the curve at the given point P and an equation of the tangent line at P.

y=x^3-9x , P(1,-8)

How can you do this without derivatives? Thanks

link: https://imgur.com/a/AR6MCoU

2 Answers

Relevance
  • 11 months ago

    y = x³ - 9x ← this is a curve, i.e. a function

    y(1) = 1 - 9 = - 8 → the representative curve of the function passes through the point P (1 ; - 8)

    y' = 3x² - 9 ← this is the derivative

    …but the derivative is too the slope of the tangent line to the curve at x

    y'(1) = 3 - 9 = - 6 ← this is the slope of the tangent line to the curve at P (1 ; - 8)

    The typical equation of a line is: y = mx + y₀ → where m: slope and where y₀: y-intercept

    The slope of the tangent line to the curve is - 6, so the equation of this tangent line is: y = - 6x + y₀

    The tangent line passes through P (1 ; - 8), so the coordinates of this point must verify the equation of the tangent line.

    y = - 6x + y₀

    y₀ = y + 6x → you substitute x and y by the coordinates of the point P (1 ; - 8)

    y₀ = - 8 + 6

    y₀ = - 2

    The equation of the tangent line to the curve at P (1 ; - 8) is: y = - 6x - 2

  • 11 months ago

    f'(x) => [f(x + h) - f(x)]/h

    f(x + h) = (x + h)³ => x³ + 3x²h + 3xh² + h³ - 9(x + h)

    Hence, f(x + h) - f(x) = x³ + 3x²h + 3xh² + h³ - 9x - 9h - x³ + 9x

    i.e. 3x²h + 3xh² + h³ - 9h 

    Then, [f(x + h) - f(x)]/h => (3x²h + 3xh² + h³ - 9h)/h

    Hence, 3x² + 3xh + h² - 9

    As h --> 0, 3x² + 3xh + h² - 9 --> 3x² - 9

    So, gradient function is 3x² - 9

    Then, at x = 1 we have:

    f '(1) = -6

    At the point (1, -8) we have:

    y - (-8) = -6(x - 1)

    or, y + 8 = -6x + 6

    i.e. y = -6x - 2

    :)>

Still have questions? Get your answers by asking now.